Anomalous yield behavior of hypo- and hyper-stoichiometric Fe3Al intermetallic compounds - Park, JW (ELSEVIER SCI LTD, 2002)
Compression tests were performed using a computerized deformation apparatus to clarify the effect of order-disorder transformation modes on the anomalous yield behavior of Fe3Al intermetallic compounds. Alloys of two different compositions, 24.1 and 27.2 at.% Al, were investigated at room and elevated temperature after heat treatment in various phase fields. The two alloys showed different dependence of anomalous yield behavior on the test temperatures. At elevated temperatures, the hypo-stoichiometric alloy revealed a peak in yield stress in the alpha + D0(3) region, while hyper-stoichiometric alloy showed remarkable strengthening in the D0(3) region and a peak yield stress in the B2 region. In the case of the room temperature test, however, the hyper-stoichiometric alloy exhibited a minimum yield stress in the B2 region near the D0(3)-B2 transformation temperature, and the hypo-stoichiometric alloy showed a peak in the a + D0(3) region. It is considered that not only the change in the degree of order but also precipitation hardening is governing factors for the anomalous strengthening of the hypo-stoichiometric alloy at room and elevated temperatures. In contrast, the change in the degree of order and thermal energy is believed to control the yield behavior of the hyper-stoichiometric alloy through a thermally activated dislocation transition mechanism, resulting in the opposite behavior at room and elevated temperatures. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: IRON-ALUMINUM ALLOYS; FE-AL ALLOYS; ORDER-DISORDER TRANSFORMATION; STRESS; DISLOCATIONS; EQUILIBRIA